Correction: Taleb et al. Measurement and Evaluation of Voltage Unbalance in 2 × 25 kV 50 Hz High-Speed Trains Using Variable Integration Period. Electricity 2024, 5, 154–173 - Yassine Taleb; Roa Lamrani; Ahmed Abbou (Electricity)
There was an error in the original publication [...]